Pathways to Detection of Strongly-Bound Inorganic Species: The Vibrational and Rotational Spectral Data of AlH2OH, HMgOH, AlH2NH2, and HMgNH2 - Watrous, Alexandria G.; Davis, Megan C.; Fortenberry, Ryan C. (Frontiers in Astronomy and Space Sciences, 2021)
Small, inorganic hydrides are likely hiding in plain sight, waiting to be detected toward various astronomical objects. AlH2OH can form in the gas phase via a downhill pathway, and this high-level quantum chemical study shows that this molecule exhibits bright infrared features for anharmonic fundamentals in regions above and below that associated with polycyclic aromatic hydrocarbons. AlH2OH along with HMgOH, HMgNH2, and AlH2NH2 are also polar with AlH2OH having a 1.22 D dipole moment. AlH2OH and likely HMgOH have nearly unhindered motion of the hydroxyl group but are still strongly bonded. Such likely assists in gas phase synthesis where aluminum oxide and magnesium oxide minerals likely begin their formation stages with AlH2OH and HMgOH. This work provides the spectral data necessary to classify these molecules such that observations as to the buildup of nanoclusters from small molecules can possibly be confirmed.